2023
DOI: 10.3390/diagnostics13091578
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of Larynx and Trachea in the Neonatal Period, Examination Standard with Predictive Values—Study Protocol

Abstract: Diseases of the larynx and trachea are a heterogenous group of disorders. Their diagnosis frequently requires invasive methods. Ultrasound is a non-invasive, repeatable and safe diagnostic method, which has recently, thanks to the development of technology, provided for very accurate imaging of even small structures, as well as their assessment on dynamic examination. Ultrasound examination of the larynx and trachea will be performed in 2022–2023 in a group of randomly selected 300 stable neonates born between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…These authors concluded that the accuracy of LUS increases by using quantitative measures. In turn, a study is currently underway to establish reference ranges for the sizes of individual structures of the larynx and trachea in the neonatal population (24). This study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…These authors concluded that the accuracy of LUS increases by using quantitative measures. In turn, a study is currently underway to establish reference ranges for the sizes of individual structures of the larynx and trachea in the neonatal population (24). This study has limitations.…”
Section: Discussionmentioning
confidence: 99%